(untitled) (Research, Society and Development, 2021)
Sorghum is the fifth most produced cereal in the world, but it is still used almost entirely for animal feed. It presents a great potential for human food due to its composition, for being a gluten-free cereal, and also due to agronomic aspects. For having a composition similar to corn, this work aimed to submit this cereal to treatments generally used for corn grits, extrusion and nixtamalization, evaluating the flours obtained by these treatments. Seven samples were prepared: 4 using only sorghum as raw material, 1 combined with corn grits, and 2 with corn grits as raw material. One of the sorghum samples did not undergo any treatment, one of them underwent nixtamalization, while the others were extruded. All samples were evaluated for moisture, water absorption and solubility index, fiber, protein and color content. The results show the potential that sorghum can have in human food, highlighting the high protein content, higher than in samples containing corn grits, and higher after the extrusion process. It is concluded that it is possible to produce pre-gelatinized flours from sorghum grains, with potential for food industries.